Earth Resources and Environmental Remote Sensing/Gis Applications XI 2020
DOI: 10.1117/12.2574015
|View full text |Cite
|
Sign up to set email alerts
|

The documentation of ecclesiastical cultural heritage sites in Cyprus

Abstract: Innovative digital applications are invaluable for the documentation and conservation of cultural heritage monuments. Digital techniques can provide data on cultural heritage sites to enhance understanding of their changes over time. Due to the age and conditions of cultural heritage monuments in Cyprus, especially churches, there is a great demand to develop a methodology that is capable of digitizing both the internal and external church using a variety of non-invasive techniques as a means of storing and ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…), not able to take enough photographs for construction 3D model. Thus, to eliminate these problems and construct a complete 3D model for the cultural heritage objects, studies integrated terrestrial photographs with TLS data (Guarnieri et al 2006, Guarnieri et al 2010, Owda et al 2018 or UAV data (Lo Brutto et al 2018, Lumhann et al 2020, Themistocleous et al 2020 for building a complete and accurate 3D model. All these studies indicated that combining terrestrial photographs with TLS or UAV data improves the model.…”
Section: D Models Comparison With Cloudcomparementioning
confidence: 99%
“…), not able to take enough photographs for construction 3D model. Thus, to eliminate these problems and construct a complete 3D model for the cultural heritage objects, studies integrated terrestrial photographs with TLS data (Guarnieri et al 2006, Guarnieri et al 2010, Owda et al 2018 or UAV data (Lo Brutto et al 2018, Lumhann et al 2020, Themistocleous et al 2020 for building a complete and accurate 3D model. All these studies indicated that combining terrestrial photographs with TLS or UAV data improves the model.…”
Section: D Models Comparison With Cloudcomparementioning
confidence: 99%